Enhancement of Students’ Biological Literacy and Critical Thinking of Biology through Socio-Biological Case-Based Learning - Suwono, H.; Pratiwi, H. E.; Susanto, H.; Susilo, H. (Jurnal Pendidikan IPA Indonesia, 2017)
Biology is a leading science and a foundation in everyday life for all people. Biology student teachers need to be equipped with biological literacy and critical thinking skills in order to teach biology in the future. This research is aimed at determining the effect of socio-biological case-based learning on biological literacy and critical thinking skills of biology student teachers compared with the traditional learning (lecture-based learning). Socio-biological case-based learning is a model of problem-based learning by placing biological cases as a problem to be explained and solved through a series of investigative activities. This research was a quasi-experimental conducted at the Department of Biology, Universitas Negeri Malang. The research samples were the first year students who programmed the General Biology course, consisting of 29 students as a control group and 33 students as experimental group. This research was conducted in September-December 2015. The data of biological literacy and critical thinking were collected from pre-test and post-test. The data were analyzed using ANCOVA test. The research showed that there was a significant difference of biological literacy and critical thinking skills between the students taught by using socio-biological case-based learning and those taught by using lecture-based learning. The research indicated that the socio-biological case-based learning could enhance the biological literacy and critical thinking skills of biology students teachers.